Effect of the intervention program "Paralympic School Day" on attitudes of children attending international school towards inclusion of students with disabilities [Vliv intervenčního programu "Paralympijský školní den" na postoje dětí navštěvujících mezinárodní školu vůči začlenění studentů s postižením] - Georgios Xafopoulos; Martin Kudláček; Christina Evaggelinou (Palacky University, 2009)
OBJECTIVE: The aim of this study was to investigate the effect that the "Paralympic School Day" had on the attitudes of children attending the International school in Ostrava, Czech Republic, toward the inclusion of peers with a disability in general physical education classes. METHODS: Students (71, including 42 boys and 29 girls), with a mean age of 12.70 and 11.67 years respectively, originating from 5 countries, participated in the program. All participants completed the questionnaire "Children's Attitude Toward Integrated Physical Education-Revised" (CAIPE-R) (Block, 1995) and the Adjective checklist (Siperstein, 1980) before and after the implementation of the program. The CAIPE-R questionnaire examines two areas (subscales) - general attitudes and sport specific attitudes. RESULTS: Results indicated significant differences only in general attitudes among girls measured by the Adjective checklist. Other changes were non significant. Among boys there were slight non significant positive changes in the adjective checklist (t = 0.75, p = 0.46) and in attitudes toward inclusion in PE (t = 0.61, p = 0.55) and non significant negative changes in attitudes toward the modification of sport rules (t = -0.25, p = 0.81). Among girls we found non significant negative changes in attitudes toward inclusion in PE (t = -0.64, p = 0.53) and non significant negative changes were also found in attitudes toward the modification of sport rules (t = -1.26, p = 0.22). [CÍL: Cílem této studie bylo prošetřit, jaký má "Paralympijský školní den" vliv na postoje dětí navštěvujících 1. mezinárodní školu v Ostravě vůči začlenění spolužáků s postižením do hodin tělesné výchovy. METODIKA: Programu ze zúčastnili studenti z 5 zemí (71, z toho 42 chlapců a 29 dívek) průměrného věku 12,70, respektive 11,67 let. Všichni účastníci vyplnili dotazník "Postoj dětí vůči integrované tělesné výchově - revidovaná verze" (CAIPE-R) (Block, 1995) a Adjective checklist (Siperstein, 1980), a to před implementací programu a po ní. Dotazník CAIPE-R zkoumá dvě oblasti (subškály) - obecné postoje a postoje vztahující se ke sportu. VÝSLEDKY: Výsledky naznačily významné rozdíly pouze v obecných postojích mezi dívkami, a to dle výsledků v Adjective checklist. Další změny nebyly významné. Mezi chlapci byly slabé nevýznamné pozitivní změny v Adjective checklist (t = 0,75, p = 0,46) a v postojích vůči začlenění do TV (t = 0,61, p = 0,55) a nevýznamné negativní změny v postojích vůči přizpůsobení sportovních pravidel (t = -0,25, p = 0,81). Mezi dívkami jsme zaznamenali nevýznamné negativní změny v postojích vůči začlenění do TV (t = -0,64, p = 0,53) a nevýznamné negativní změny byly také zaznamenány v postojích vůči přizpůsobení sportovních pravidel (t = -1,26, p = 0,22).]